Pengaruh Edukasi terhadap Kepatuhan Penerapan Prinsip Higiene dan Sanitasi Makanan serta Faktor Penyebab di Instalasi Gizi Rumah Sakit X - Aulia Firdausi; Amalia Rahma (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The application of food hygiene and sanitation principles is an important aspect in ensuring the quality of nutritional services in hospitals. Low compliance of kitchen staff in maintaining hygiene is often caused by a lack of supervision, motivation, and limited supporting facilities. This study aims to determine the effect of education on compliance with the application of food hygiene and sanitation and its contributing factors in the Nutrition Installation of Hospital X through an internship activity conducted in July–October 2025. The research method used a quasi-experimental model with a one-group pretest-posttest and a mixed methods approach. The research subjects were seven kitchen staff, with two of them being interviewed in depth via voice recording. Data collection was carried out through initial observations, compliance checklists, and recorded interviews at the pretest and posttest stages. Educational interventions were carried out through counseling, routine briefings, and mentoring in the six-step handwashing practice according to WHO guidelines. Data analysis was carried out using descriptive quantitative and thematic qualitative methods. The results showed an increase in staff compliance after being given education, seen from changes in behavior in washing hands properly, using personal protective equipment, and maintaining cleanliness of the work area. Based on pretest interview results, low compliance was caused by a lack of supervision due to the lack of accreditation, infrequent monitoring, the misperception that visibly clean hands were safe enough, and limited water supply due to the shared drain with the hospital laundry. Following the educational intervention, posttest results showed improved compliance compared to baseline.